2013
DOI: 10.1155/2013/305202
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Augmented Oxidative Stress in Bone Marrow Mononuclear Cells from Angiotensin-Dependent Hypertensive Mice

Abstract: It has been proposed that the nonhemodynamic effects of angiotensin II are important for the damage observed in the two-kidney, one-clip (2K1C) renovascular hypertension model. Much evidence confirms that angiotensin II is directly involved in NAD(P)H oxidase activation and consequent superoxide anion production, which can damage DNA. The current study was performed to examine the effects of angiotensin-II-dependent hypertension in bone marrow mononuclear cells (BM-MNC); dihydroethidium staining was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 78 publications
4
19
0
Order By: Relevance
“…Despite the impact of arterial hypertension on ROS production in BM cells is poorly understood in murine models, our data support the idea that 2K1C hypertension contributes to oxidative stress in BM cells, leading to unfavorable processes, such as DNA damage (Schupp et al, 2007;Campagnaro et al, 2013) and apoptosis (Endtmann et al, 2011).…”
Section: K1c Hypertension Affects Bone Marrow Cellssupporting
confidence: 82%
See 2 more Smart Citations
“…Despite the impact of arterial hypertension on ROS production in BM cells is poorly understood in murine models, our data support the idea that 2K1C hypertension contributes to oxidative stress in BM cells, leading to unfavorable processes, such as DNA damage (Schupp et al, 2007;Campagnaro et al, 2013) and apoptosis (Endtmann et al, 2011).…”
Section: K1c Hypertension Affects Bone Marrow Cellssupporting
confidence: 82%
“…Some authors, including us, have observed alterations in DNA caused by hypertension (Schupp et al, 2007;Fandos et al, 2009;Campagnaro et al, 2012Campagnaro et al, , 2013. In this work, the DNA content analysis showed that 2K1C hypertension induces DNA fragmentation in BM cells, suggesting that the disease leads to DNA changes compromising the functionality of the cells.…”
Section: Dna Contentsupporting
confidence: 49%
See 1 more Smart Citation
“…Elevated levels of ROS, which is a characteristic of a state of oxidative stress, has been reported in clinical and pre-clinical studies in many cardiovascular diseases, including diabetes, hypertension and atherosclerosis [3,11,24,34,35]. Although under physiological conditions ROS are continuously produced in most cells, the imbalance between ROS production and its degradation, can lead to genomic instability and, consequently, permanent changes in the genetic material, contributing to unfavourable processes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This increased ratio is an indicator of enhanced cell survival [34]. Bone marrow is the major reservoir for adult organ-specific stem cells, including endothelial progenitor cells, hematopoietic stem cells, and mesenchymal stem cells [35]. Consequently, it is reasonable to propose that BM mesenchymal stem cells may be locally activated in livers of the irradiated rats and compensated the damaged cells.…”
Section: Discussionmentioning
confidence: 99%